THE CONCEPT OF MANAGEMENT ACCOUNTING AS AN INFORMATION SYSTEM IN THE MANAGEMENT OF COMMERCIAL ORGANIZATION PROFIT - E. Kyshtymova; N. Lytneva (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
In the conditions of reforming of the mechanism of management there is a problem of the qualitative, reliable information necessary for regulation of economic processes with a view of maximizing profit of the commercial organizations. One of the concept directions improvement of accounting system is development of management accounting which is directed on ensuring control of profitability of the current activity of the organization first of all regarding decrease in expenses, an assessment of efficiency of managing as a whole and in a cut of divisions of the organization, the analysis of profitability of separate sectors of activity and market segments.